2017
DOI: 10.31224/osf.io/94s8d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Heavy Working Fluids on Hydrogen Combustion

Abstract: Abstract:The thermodynamic efficiency of internal combustion engines is dependent on the compression ratio and specific heat ratio of the working fluid. Using a mixture of oxygen and noble gases instead of air can increase the thermal efficiency due to their higher specific heat ratio. It also has advantage of eliminating NOx caused by lack of nitrogen. In this study, the three dimensional turbulent injection of hydrogen into a constant volume combustion chamber has been modeled and compared to mixtures of oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…To address these concerns, combustion systems have evolved over time, implementing a wide variety of approaches. Fuels are broadly utilized in premixed [1][2][3][4] and non-premixed combustion [5][6][7][8][9] using gas turbines and different forms of internal combustion (IC) engines such as spark ignition (SI) [10][11][12], homogeneous charge compression ignition (HCCI) [13][14][15], and reactivity controlled compression ignition (RCCI) [16,17]. Natural gas, as one of the cleanest fossil fuels, is one of the main sources of energy production and electricity generation in the United States and abroad.…”
Section: Introductionmentioning
confidence: 99%
“…To address these concerns, combustion systems have evolved over time, implementing a wide variety of approaches. Fuels are broadly utilized in premixed [1][2][3][4] and non-premixed combustion [5][6][7][8][9] using gas turbines and different forms of internal combustion (IC) engines such as spark ignition (SI) [10][11][12], homogeneous charge compression ignition (HCCI) [13][14][15], and reactivity controlled compression ignition (RCCI) [16,17]. Natural gas, as one of the cleanest fossil fuels, is one of the main sources of energy production and electricity generation in the United States and abroad.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent experimental study has been carried out on the effect of noble gases on fuel propagation and thermal characteristics of gaseous direct injection; it has been shown that argon can be a potentially beneficial alternative working fluid [12]. In another study, penetration length, cone angle, mixedness, and flame properties have been extensively studied for hydrogen injection into different working fluids by numerical modeling, indicating that replacing nitrogen with argon and xenon can dramatically change the jet development in the chamber [13].…”
Section: Introductionmentioning
confidence: 99%
“…Constant volume combustion chambers (CVCC) are typically used in order to investigate fundamental aspects of combustion phenomena such as premixed ignition [1][2], diffusion flames, laminar flame speed [3], turbulent flame speed, autoignition [4][5], injection strategies [6][7][8], and emissions formation [9]. In this study, a small test stand is placed at the bottom of the cylindrical CVCC for conducting materials synthesis experiments, initially focused on the creation of paper-templated metals.…”
Section: Introductionmentioning
confidence: 99%